The National Physician Assistant Program Profile, 1975-76 [First Edition] - Association of Physician Assistant Programs (Association of Physician Assistant Programs, 1974)
This is the first issue of the Association of Physician Assistant Programs (APAP) profile of member programs. The program was marketed to perspective students to help them understand admission requirements. The profile contains chapters on planning for the PA profession, admission procedures, financial information, nature of PA education, national certification of PAs, legal aspects, accreditation, an overview of programs at a glance, and detailed information about each of the 44 PA programs listed in the profile. There was an estimated 1,400 PA graduates at the time and tuition averaged $10,000 to $14,000 per annum.